Characterization of an Endemic Plant Origanum grosii from Morocco: Trace Element Concentration and Antihyperglycemic Activities - H. El hassouni; M. Bouhrim; R. El hajji; M. Bnouham; A. Ziyyat; A. Romane (Journal of Chemistry)
Origanum genus is one of the most widely used herbs in folk medicine for its biological properties. The present investigation aims to characterize, for the first time, endemic Origanum grosii collected from the Taounate region, Morocco. This characterization was realized by determining the concentration of metals in different parts of the plant (flowers, leaves, and stems) by ICP-MS, and the results were studied statistically by Principal Component Analysis (PCA). Phytochemical screening with the dosage of polyphenols and flavonoids has been conducted. To know more about this species, antihyperglycemic tests have been performed to highlight the presence or absence of the antidiabetic effect for this plant. An Oral Glucose Tolerance Test (OGTT) has been performed on normal mice which were divided into two groups of six mice each. Group 1 (control group) was treated with distilled water, and group 2 was treated with an aqueous extract of O. grosii by gavage at 150 mg/kg. Digestive enzyme α-amylase inhibition assay has also been evaluated to study the inhibition effect of the studied extract using acarbose as a control. The results showed that the leaves exhibited a high concentration of trace elements (Ca, Mg, and K) and total absence of heavy metals, which were found in small quantities (Cr, Ni, and B) on the stems, and this makes the plant safe to use. On the other hand, tannins, flavonoids, triterpenes, and steroids were the major families strongly present in this species. The antidiabetic results showed that O. grosii have significantly reduced postprandial hyperglycemia after glucose loading in normal rats. It showed also that this species has a significant antihyperglycemic activity reflected by the inhibition of α-amylase. The one responsible for this property could be the synergy between the trace elements and the nature of the chemical families of O. grosii species, which can make this plant useful in the management of postprandial hyperglycemia.